2022
DOI: 10.1007/s00228-021-03267-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilisation in neonatal units in England and Wales: a national cohort study

Abstract: Purpose To describe drug utilisation patterns in neonatal units. Methods Retrospective observational cohort study using data held in the National Neonatal Research Database (NNRD) for neonatal units in England and Wales including infants born at 23 to 44 weeks’ gestational age (GA) from 01 January 2010 to 31 December 2017. Results The cohort included 17,501 (3%) extremely preterm infants; 40,607 (7%) very preterm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Caffeine is the most frequently prescribed medicine in neonates 1. The Caffeine for Apnea of Prematurity (CAP) trial showed that, in very low birthweight infants, caffeine reduces the risk of bronchopulmonary dysplasia (BPD), and improves the rate of survival without neurodevelopmental impairment at 18–21 months of age 2.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is the most frequently prescribed medicine in neonates 1. The Caffeine for Apnea of Prematurity (CAP) trial showed that, in very low birthweight infants, caffeine reduces the risk of bronchopulmonary dysplasia (BPD), and improves the rate of survival without neurodevelopmental impairment at 18–21 months of age 2.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine citrate is one of the most widely prescribed drugs in neonatology ( 106 ) and reduces the rates of BPD, intraventricular hemorrhage, and neurodevelopmental impairment among preterm infants ( 107 ). The Caffeine for Apnea of Prematurity trial for the use of caffeine citrate in preterm infants attributed the increased incidence of BPD among its control group to the extended time this group required positive pressure ventilator support ( 108 ).…”
Section: Impact Of Bpd Therapies On Tgf-β Signalingmentioning
confidence: 99%
“…In the UK, the percentage of very preterm infants who receive intravenous morphine increased from 32% in 2010 to 37% in 2017. 13…”
Section: Pain In Preterm Infantsmentioning
confidence: 99%
“…36 37 In an update of medication prescribing patterns in the US NICUs, Stark et al reported that between 2010 and 2018, dexmedetomidine was ninth in the list of drugs that had the greatest relative increase in use and had become the 90th most frequently prescribed medication 38 although its use was not reported, at least until 2017, in neonatal care in the UK. 13 Dexmedetomidine is used for sedation and analgesia on its own or in combination with other agents with the aim of reducing cumulative exposure to opioids and benzodiazepines. Comparing 48 infants with a mean GA of 25 weeks who received either fentanyl or dexmedetomidine, O'Mara et al found that the dexmedetomidine group required less adjunctive sedation.…”
Section: Clinical Reports Of the Use Of Dexmedetomidine In Preterm In...mentioning
confidence: 99%